Environmental stressors in Amazonian riverine systems - Val, Adalberto Luis; Duarte, Rafael Mendonça [UNESP]; Campos, Derek; de Almeida-Val, Vera Maria Fonseca (Elsevier, 2022)
The Amazon has a rich history of tectonic and climatic effects that have given rise to vast, complex and dynamic interconnected landscapes. The dynamics of the system can be observed today by the oscillation of river water levels, variations in oxygen levels, pH and temperature, and the biological diversity that exists in the different systems throughout the year. This continuous environmental diversity has contributed to the emergence of a rich ichthyofauna that has developed a vast set of adaptations at all levels of biological organization to cope with the continuous environmental challenges of the biome. However, the environmental structure that was formed over some 65 million years, i.e., since the beginning of the Andes uplift, is today confronted with many challenges of a, shall we say, new era—the Anthropocene. These challenges include metal pollution, urban pollution, pesticides, oil, hydroelectric construction, and, most importantly, the effects of climate change. Many of the evolutionary adaptations incorporated by fish are not sufficient to neutralize the effects of these new challenges, many of which have synergistic effects with each other or with the natural challenges that occur in the Amazon (hypoxia, low pH, low ionic availability, naturally warmer waters). Thus, it is important that we can anticipate the responses of Amazonian fishes to the challenges imposed by their environments in order to better manage the Amazon rainforest.
Keywords: Amazonian waters; Anthropogenic threats; Aquatic biota; Fish diversity; Global warming; Physiological adaptations